Hubungan Asupan Gizi dengan Kejadian Stunting pada Balita di Desa Miruk Lamredeup Kecamatan Baitussalam Kabupaten Aceh Besar - Fauziah Fauziah; Muhammad Daud; Akmalia Akmalia (Jurnal Ventilator, 2024)
The good growth period for children aged 7-12 years can be determined by providing nutritional needs in terms of quality and quantity of food and drink consumption levels. Children aged 6-7 years are vulnerable to nutritional deficiencies with nutritional status that can interfere with their development and growth. The aim of the research is to determine the relationship between nutritional intake and the incidence of stunting among toddlers in Miruk Lamredeup Village, Baitussalam District, Aceh Besar Regency. The type and design of this research uses quantitative methods through a cross sectional approach. The population in this study were 64 children aged 1-5 years in Miruk Lamredeup Village, Baitussalam District, Aceh Besar Regency. The sample in this study used Total Sampling, so the sample in the study was 64 children and parents. This research was carried out in Baitussalam District, Aceh Besar Regency. This research was carried out from 01 to 14 May 2024. The results of the research were that there was a relationship between nutritional intake and the incidence of stunting in toddlers in Miruk Lamredeup Village, Baitussalam District, Aceh Besar Regency with a value of p = 0.035. Researchers hope that the parents of respondents can improve the health and quality of life of toddlers by providing appropriate nutritional intake